Career education and experiential learning - Chiko, Carl H.; Marks, Stephen E. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper identifies some career education assumptions, describes the characteristics of experiential learning, and illustrates how experiential learning is suited to address the career education assumptions. These assumptions focus on work values; self understanding; personal, occupational and socio-economic information; academic, decision-making and job skills; and adaptability. Involvement, relevance and participant responsibility generated by experiential learning a recompatible with the career education assumptions. An example is provided to illustrate this compatability. Experiential learning is career education.